Implementation of the Child-Friendly City Policy in Bengkulu: An Analysis of Child-Friendly Play Spaces Provision: Implementasi Kebijakan Kota Layak Anak di Bengkulu: Analisis Penyediaan Ruang Bermain Ramah Anak - Junanti, Dwi Fitriani; Bangsu, Tamrin; Rosi L Vini Siregar (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
Child-Friendly Play Spaces (CFPS) are critical indicators of Child-Friendly City (CFC) implementation, yet significant gaps persist between policy and practice. This study will address the progress gap in the CFSP in Bengkulu City based on George C. Edward III's understanding of policy implementation. The researcher investigates the issue qualitatively, conducting in-depth interviews, direct observation of CFPS in 13 locations, and document analysis using a qualitative approach. An examination of the technical standards of the CFPS and the Ministry of Women's Empowerment and Child Protection indicates that none of the CFPS are compliant. This study faces four obstacles: a lack of inter-agency relationships, with only two or three meetings throughout the year; a lack of human and financial support; a lack of appropriate and positive disposition from implementers who focus on achieving administrative objectives rather than substantive targets; and a weak bureaucratic structure due to the absence of Standard Operating Procedures. This study adds to the literature on policy implementation by describing the phenomenon of decoupling by detailing the recognition of the administrative side of implementation (six consecutive Pratama awards) and the lack of quality on the substantive side of implementation. The study recommends institutional transformation, capacity building, adequate budget allocation, and systematic cross-sectoral coordination to genuinely fulfill children's rights to safe and appropriate play spaces.